The convergent trajectories of bird communities along ecological successions in european forests - Blondel, Jacques; Farré, H. (Oecologia, 1988)
There is much more variation in the composition of bird communities in the earlier open and semi-open seral stages of ecological successions in forested landscapes of Europe than later on in preforested and forested climactic stages. The demonstration of this trend is achieved from the study of four habitat gradients, two in the mediterra- nean region (Provence and Corsica) and two in central Eu- rope (Burgundy, France and Poland). A multivariate analy- sis has been used to illustrate the dynamics of communities along these successions. Displays of the results in bivariate space as well as an illustration of the distributional profiles of some of the most characteristic species show that: i) there is a discrimination between the two mediterranean gradients and the two medioeuropean ones and ii) each succession starts with a very distinct set of species and then the four gradients regularly converge in the last climactic stage where there is almost no discrimination between com- munities. These results are discussed in the light of the histo- ry of European biotas during the Pleistocene. The reason why there is more variation in species composition in the earlier seral stages than in the later forested stages are dis- cussed according to current theories on the role of habitat selection on speciation processes.
Keywords: Community dynamics; Ecological succession; historical biogeography; Mediterranean; speciation